Conformation of Lysine Vasopressin: A Comparison with Oxytocin - Walter, Roderich (1972)
Starting with assignments of proton nuclear magnetic resonance previously made for oxytocin in deuterated dimethylsulfoxide at 220 MHz, we have assigned resonances for the mammalian antidiuretic hormone, lysine vasopressin. The results demonstrate that spectral assignments of neurohypophyseal hormones and their congeners can, within certain limits, be derived from each other. Comparison of the spectra of lysine vasopressin and oxytocin suggests that the gross backbone conformations of their 20-membered ring components are for the most part similar in deuterated dimethylsulfoxide, whereas the C-terminal acyclic amino-acid sequence of lysine vasopressin is more flexible than that of oxytocin.